Introduction of Integrated Pest Management Practices in Urban Farming in Mataram City During the Covid-19 Pandemic - Muhammad Sarjan; Moh Taufik Fauzi; Ruth Stella P. Thei (Pascasarjana Universitas Mataram, 2022)
The outbreak of the COVID-19 pandemic has encouraged people to adopt a healthier lifestyle and at the same time carry out a number of environmentally friendly activities such as urban farming. Besides helping to guarantee the food security aspect of urban areas, urban farming also helps create green open spaces. Even so, urban farming also has a negative impact, if it is carried out with a system that is not wise and effective, such as it can cause increased noise pollution, air pollution, flooding, water wastage, and even potential as a breeding ground for mosquitoes that transmit various diseases. Therefore, it is necessary to educate the public about various aspects needed in the implementation of urban farming, one of which is how to implement Integrated Pest Management (Known as PHT). The method used in this activity is the Action Research Method by applying the Participatory Action Program approach from the participants through discussion, and group work in all activities. The results of group discussions at KWT Bunga Matahari, and other urban farming groups in Kekalek and in Ampenan show that the majority of urban farming communities are very interested in developing various types of fresh vegetables and fruit in their yards as part of the Department of Sustainable Food Home Areas (KRPL) program. Food Security of the Province of NTB and the City of Mataram. Group discussions also revealed that group members became more active during the COVID-19 pandemic, especially during WFH in the early days of the pandemic. They feel the benefits of farming activities in the yard because it really helps meet the family's food needs, especially fresh vegetables. However, most of the target group members are still not familiar with environmentally friendly cultivation techniques, especially in terms of integrated pest management. Although in fact, they are not aware that there are several activities that include PHT, such as monitoring, planting ornamental plants (refugia) around vegetable crops, and mechanical control by directly killing pests that attack their plants